Land Functions, Rural Space Governance, and Farmers’ Environmental Perceptions: A Case Study from the Huanjiang Karst Mountain Area, China - Jiangjun Wan; Yi Su; Huanglin Zan; Yutong Zhao; Lingqing Zhang; Shaoyao Zhang; Xiangyu Dong; Wei Deng (Land, 2020)
Residents of rural areas live and depend on the land; hence, rural land plays a central role in the human–land relationship. The environment has the greatest direct impact on farmers’ lives and productivity. In recent years, the Chinese government carried out vigorous rural construction under a socialist framework and implemented a rural revitalization strategy. This study was performed in a rural area of Huanjiang County, Guangxi Province, China. We designed a survey to measure rural households’ perceptions of three types of rural spaces: ecological, living, and production spaces. The survey was administered to 379 farmers, and their perceptions and satisfaction with Ecological–Living–Productive spaces were evaluated with the use of structural equation modeling. Analysis of latent and observed variables indicates that: (1) Farmers’ overall satisfaction with Ecological–Living–Productive spaces was moderate. The average satisfaction score for production spaces was lowest (2.881) while that for living spaces was highest (3.468) and that for ecological spaces was in between (3.351). (2) The three most important exogenous observed variables associated with living space satisfaction were house comfort > domestic water supply > domestic sewage treatment. The three most important exogenous observed variables associated with production space satisfaction were irrigation water > cultivated land quantity > cultivated land fertility. The three most important exogenous observed variables associated with ecological space satisfaction were garbage disposal > vegetation cover > flood and waterlogging. Based on the requirements of the rural revitalization strategy and the results of our analyses of rural households’ spatial perceptions, we propose corresponding countermeasures and suggestions.